175 A disappearing act: a tale of immunosuppression, EBV and CNS B-cell lymphoma. Issue 3 (9th February 2012) - Doherty, C; Hunt, S J; Toner, P; Sheehy, O M; Healy, E
Abstract : This 41-year-old woman with proven Ulcerative Colitis had been managed with Asacol, Prednisolone and Azathioprine. Eighteen months after commencement of Azathioprine (2 mg/kg/day) she developed a sub-acute severe encephalopathy. Azathioprine was discontinued on transfer to the Neurology unit. MRI imaging demonstrated numerous subcortical cerebral and cerebellar lesions. The differential diagnosis included an atypical infective process or metastases. CSF was normal with no cytological evidence of malignancy. JC virus, HIV negative. CT of chest abdomen and pelvis showed pulmonary nodules and bilateral adrenal masses. Adrenal biopsies/bronchoscopy normal. Serial MRI over 10 weeks demonstrated marked improvement except for an enlarging cerebellar lesion. Her condition greatly improved. Biopsy of the cerebellar lesion demonstrated B-Cell Lymphoma with marked EBV staining. Bone marrow examination was normal. A diagnosis of limited CNS B-Cell Lymphoma was made. Spontaneous resolution of the persistent cerebellar lesion was observed at follow-up. Follow-up whole body CT-PET was normal. Nine months post discharge she works full time and has no neurological deficit. We propose that withdrawal of immunosuppression allowed for an "immune reconstitution" leading to resolution of her malignancy. Clinicians need to recognise the potential for self-resolution in similar scenarios to avoid unnecessary exposure to potentially toxic therapies.